ANALISIS PERENCANAAN OVERLAY PADA RUAS JALAN CRAKEN-NGULUNGKULON NAMBAK-NGULUNGKULON DENGAN BAHAN ACL PADA STA 0.00-13.345 KECAMATAN MUNJUNGAN KABUPATEN TRENGGALEK - Wisnu Arganata; Arthur Daniel Limantara; Yosef Cahyo; Agata Iwan Candra (Faculty of Engineering, Kadiri University, 2019)
Nowadays, the development of road capacity and vehicle quantity and the lack of optimal traffic infrastructure operations are the main problems in the Nambak-Ngulungkulon Craken-Ngulungkulon road section. This road is the object of observation because the road is an integrated system of the Nambak-Ngulungkulon Craken-Ngulungkulon road network. It is necessary to analyze how the performance and the thickness of the flexible pavement layer needed. To analyze road performance and calculate pavement thickness, the writer uses the Bina Marga 2017 method with ACL material at STA 0.00 - 13,345. The results of the analysis and calculation for the geometric planning of the Nambak-Ngulungkulon Craken-Ngulungkulon road section obtained the value of surface course with the 2017 Bina Marga method of 13 cm. Overlay work on the planning age is carried out in the 15 the year with an additional layer thickness with the Bina Marga 2017 method of 3 cm. And the traffic growth rate increased by 28.65% for 10 years y.a.d.Saat ini pengembangan kapasitas jalan dan kuantitas kendaraan dan kurangnya operasi infrastruktur lalu lintas yang optimal adalah masalah utama di ruas jalan Nambak-Ngulungkulon Craken-Ngulungkulon. Jalan ini adalah objek pengamatan karena jalan tersebut merupakan sistem yang terintegrasi dari jaringan jalan Nambak-Ngulungkulon Craken-Ngulungkulon. Perlu untuk menganalisis bagaimana kinerja dan ketebalan lapisan perkerasan lentur yang dibutuhkan. Untuk menganalisis kinerja jalan dan menghitung tebal perkerasan, penulis menggunakan metode Bina Marga 2017 dengan material ACL di STA 0,00 - 13,345. Hasil analisis dan perhitungan untuk perencanaan geometrik ruas jalan Nambak-Ngulungkulon Craken-Ngulungkulon diperoleh nilai permukaan jalan dengan metode Bina Marga 2017 13 cm. Pekerjaan overlay pada usia perencanaan dilakukan pada tahun ke-15 dengan tambahan ketebalan lapisan dengan metode Bina Marga 2017 3 cm. Dan tingkat pertumbuhan lalu lintas meningkat sebesar 28,65% selama 10 tahun y.a.d.